‘Cellphilms’ and ‘photovoice’: How visual tools can help understand farmers’ adaptation to climate change - Kawerau, Laura; Birner, Regina (DLG-Verlag GmbH, 2020)
Use of mobile phones holds great promise for identifying and understanding gendered climate change adaptation strategies in rural areas of the Global South. Our authors describe the methodology and results of a case study with women, men and youth farmers in Uganda demonstrating the benefits and challenges that need to be addressed.